Exporting Perilous Pauline : Pearl White and serial film craze - Dahlquist, Marina (Women and film history international., 2013)
The American action film serials of the 1910s featured exciting stunts, film tricks, and effects set against the background of modern technology, often starring resourceful female heroines who displayed traditionally male qualities such as endurance, strength, and authority. The most renowned of these "serial queens" was Pearl White, whose career as the adventurous character Pauline developed during a transitional phase in the medium. This collection of essays explores the serial genre and its narrative patterns, marketing, and cultural reception, and historiographic importance.